Mendiagnosa Penyakit Ginjal Menggunakan Metode Certainty Factor - Ramos Parulian Ambarita; Rusmin Saragih; Husnul Khair (Bulletin of Multi-Disciplinary Science and Applied Technology, 2023)
In the current era of technological advancement, rapid developments are occurring in Artificial Intelligence (AI), including the concept of Expert Systems. Expert Systems allow knowledge from experts in a field to be integrated into a computer programme to make intelligent decisions. The use of this technology, particularly in healthcare such as common kidney diseases, has great potential in diagnosis and treatment. As a vital organ, the kidney plays an important role in the body, but if it malfunctions, it can cause a number of problems. One method used to address uncertainty in expert thinking is Certainty Factor, which tests the certainty of data or facts. With AI and Expert Systems, it is hoped that healthcare services can be improved, supporting the treatment of kidney disease and other health problems.